Targeted next generation sequencing revealed a novel deletion-frameshift mutation of KCNH2 gene in a Chinese Han family with long QT syndrome: A case report and review of Chinese cases. Issue 16 (April 2020) - Du, Fengli; Wang, Guangxin; Wang, Dawei; Su, Guoying; Yao, Guixiang; Zhang, Wei; Su, Guohai
Abstract: Introduction: Long QT syndrome (LQTS) is electrocardiographically characterized by a prolonged QT interval and manifests predisposition to life-threatening arrhythmia which often leads to sudden cardiac death. Type 2 LQTS (LQT2) is the second most common subtype of LQTS and caused by mutations in KCNH2 gene. Up to date, >900 mutations have been reported to be related to LQT2. However, mutational screening of the KCNH2 gene is still far from completeness. Identification of KCNH2 mutations is particularly important in diagnosis of LQT2 and will gain more insights into the molecular basis for the pathogenesis of LQT2. Patient concerns: A Chinese Han family with LQTS phenotypes was examined. Diagnosis: A novel deletion-frameshift mutation, c.381_408delCAATTTCGAGGTGGTGATGGAGAAGGAC, in exon 3 of KCNH2 gene was identified in a Chinese family with LQTS. On the basis of this finding and clinical manifestations, the final diagnosis of LQT2 was made. Interventions: Next-generation sequencing (NGS) of DNA samples was performed to detect the mutation in the LQTS-related genes on the proband and her mother, which was confirmed by Sanger sequencing. The proband was then implanted with an implantable cardioverter defibrillator and prescribed metoprolol 47.5 mg per day. Outcomes: This novel heterozygous mutation results in a frameshift mutation after the 128 th residue (Asparagine), which replaced the original 1031 amino acids with 27 novel amino acids (p.N128fsX156). Conclusion: This novel mutation presumably resulted in a frameshift mutation, p.N128fsX156. Our data expanded the mutation spectrum of KCNH2 gene and facilitated clinic diagnosis and genetic counseling for this family with LQTS.